Replacing corn silage with extruded forage in sheep feeding - Silva, Débora Adriana de Paula; Loreno, Matheus Borges Naves; Schultz, Erica Beatriz; Siqueira, Marco Tulio Santos; Oliveira, Karla Alves; Macedo Júnior, Gilberto de Lima (Acta Scientiarum. Animal Sciences, 2022)
The objective was to evaluate levels of replacement of corn silage with extruded forage (Foragge®) in sheep feeding. Twenty adult Santa Inês ewes in maintenance, and 55.8 kg average weight were housed in metabolic cages, and the treatments consisted of 20, 40, 60 and 80% replacement of corn silage with Foragge® extruded forage with 60% Uruchloa brizantha in the diet. The design was completely randomized, with regression analysis and non-parametric analysis at 5% probability. The supply of up to 80% extruded roughage to replace corn silage increased dry matter intake and digestibility, and fecal output in dry matter (p < 0.05). Also, it increased the efficiency of ingestion, rumination and chewing activities of sheep, but did not alter urinary parameters and energy metabolites (p > 0.05). However, it reduced the concentration of uric acid (p < 0.05). Foragge® extruded roughage can replace corn silage by up to 80% with changes in intake, digestibility, fecal parameters, ingestive behavior and concentration of uric acid and urea, with no modifications in urinary parameters and energy metabolites.